Psychosocial resources moderate the association between stress and insomnia among patients with digestive system cancers. Issue 2 (7th February 2023) - Lv, Gaorong; Zhao, Di; Xie, Zihui; Zhang, Yunxue; Li, Yuanyuan; Mao, Cui; Dong, Xiaoling; Li, Ping
ABSTRACT: This study explored the profiles of psychosocial resources combined with resilience and family care, and analyzed their moderating effects on the relationship between stress and insomnia in patients with digestive system cancers. A total of 366 patients were recruited to participate in this study from two tertiary hospitals in China. They were assessed using the Perceived Stress Scale – 4 items, Insomnia Severity Index, Family Concern Index Questionnaire, and 10-item Connor–Davidson Resilience Scale. Latent profile analysis and the BCH (Bolck, Croon & Hagenaars) method were used to identify the subtypes and estimate the moderating role of psychosocial coping resources. About 62.3% of participants had insomnia symptoms. Insomnia was positively correlated to the stress ( r = 0.25, P < 0.001). The latent classes were the low resources class (32.8%), the medium resources class (46.1%), and high resources class (21.1%). Among these, in low (estimate value = 0.563, P = 0.003) and medium (estimate value = 0.301, P = 0.029) resources class, stress had an effect on insomnia. There was no association between stress and insomnia in high resources class (estimate value = 0.165, P = 0.637). Stress might be associated with to insomnia problems, whereas patients with high psychosocial resources are more not vulnerable. Interventions to improve family function and resilience could contribute to easing the insomnia of patients with digestive system cancers.